Molly Q's trashy travels through the water cycle. - Newcomb, Kristene frey50; Newcomb, Kristene (Folsom, NM Folsom Fallies Press, 2007)
Molly Q, the water drop, takes us on a visual journey through the water cycle.
Includes glossary.
Keywords: Water cycle -- juvenile literature